A novel material point method (MPM) based needle-tissue interaction model. Issue 12 (6th October 2021) - Li, Murong; Lei, Yong; Gao, Dedong; Hu, Yingda; Zhang, Xiong
Abstract: Needle-tissue interaction model is essential to tissue deformation prediction, interaction force analysis and needle path planning system. Traditional FEM based needle-tissue interaction model would encounter mesh distortion or continuous mesh subdivision in dealing with penetration, in which the computational instability and poor accuracy could be introduced. In this work, a novel material point method (MPM) is applied to establish the needle-tissue interaction model which is suitable to handle the discontinuous penetration problem. By integrating a hyperelastic material model, the tissue deformation and interaction force can be solved simultaneously and independently. A testbed of needle insertion into a Polyvinyl alcohol (PVA) hydrogel phantom was constructed to validate both tissue deformation and interaction force. The results showed the experimental data agrees well with the simulation results of the proposed model.